1994
DOI: 10.1084/jem.179.3.831
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of all epithelial elements during skin regeneration by keratinocyte growth factor.

Abstract: SummaryKeratinocyte growth factor (KGF), a recently discovered 18.9 kD member of the fibroblast growth factor family has been shown to selectively induce keratinocyte proliferation and differentiation in tissue culture. To explore its potential stimulating keratinocyte growth and differentiation in vivo, we analyzed for the influence of KGF on epithelial derived elements within a wound created through the cartilage on the rabbit ear. KGF accelerated reepithelialization (p = 0.004) and increased the thickness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
92
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(93 citation statements)
references
References 31 publications
0
92
0
Order By: Relevance
“…This might be explained by the overall effect of KGF on all epithelial elements, including hair follicles. 26,48 It is worth mentioning that this fur condition is only temporary and returns to normal within a few days after cessation of the treatment. Considering this mild side effect, the effect on the small intestine and taking into account some reports about KGF post-treatment not adding to overall survival, 46,31 it might be wise to examine whether a short pretransplant KGF treatment is sufficient to prevent lethal GVHD in our setting.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This might be explained by the overall effect of KGF on all epithelial elements, including hair follicles. 26,48 It is worth mentioning that this fur condition is only temporary and returns to normal within a few days after cessation of the treatment. Considering this mild side effect, the effect on the small intestine and taking into account some reports about KGF post-treatment not adding to overall survival, 46,31 it might be wise to examine whether a short pretransplant KGF treatment is sufficient to prevent lethal GVHD in our setting.…”
Section: Discussionmentioning
confidence: 97%
“…KGF is a member of the fibroblast growth factor family, also designated as FGF-7, that specifically influences epithelial cells in vivo and in vitro. 25 KGF induces proliferation in keratinocytes, 26 type II pneumocytes, 27 hepatocytes and gastrointestinal (GI) epithelial cells. 28 It has also been demonstrated that KGF can enhance survival of crypt stem cells 29 and might thus be used to protect the GI mucosa when administered prior to conditioning.…”
mentioning
confidence: 99%
“…However, other experimental approaches will be required to fully define the precise nature of KGF involvement in epithelial development. In this regard, earlier cell and organ culture studies have demonstrated that KGF is a paracrine mitogen for epithelial cells from a variety of different sources (Aaronson et al, 1991;Marchese et al, 1990;Pierce et al, 1994;Rubin et al, 1989;Ulich et al, 1994), as well as a morphogen in the ductal branching morphogenesis of the neonatal mouse seminal vesicle (Alarid et al, 1994) and the neonatal rat prostate (Sugimura et al, 1993). The extension of similar studies to other organ systems will provide a powerful approach in further elucidating the multiple roles of KGF during development.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine seems to specifically act on epithelial cells, inducing proliferation, differentiation and migration. [143][144][145] After skin injury mRNA transcription for KGF is induced in the dermis of the wound margin and in the hypodermis below the wound ground. Messenger RNA for the KGF receptor is induced in the epidermis.…”
Section: Keratinocyte Growth Factor (Kgf)mentioning
confidence: 99%